Teacher perceptions of influence, autonomy, and satisfaction in the early Race to the Top era - Kim B. Wright; Samantha M. Shields; Katie Black; Manjari Banerjee; Hersh C. Waxman (Education Policy Analysis Archives, 2018)
In the present study, hierarchical linear modeling with random intercept models was used to estimate the impact school and teacher-level factors had on K-12 teachers’ perceptions of school influence, curricular and pedagogical autonomy, and job satisfaction in the early years of the Race to the Top Era. The main predictors investigated were whether students’ standardized test scores were used as a component of either a teacher’s formal teacher evaluation or compensation, as well as whether teachers worked in a Race to the Top state. Additional school- and teacher-level predictors included percentage minority teachers and students, urbanicity of the school, teacher grade band, years teaching experience, and annual base salary. The study’s findings include statistically significantly yet small, negative correlations between teaching in a RTTT Phase I or II state at the time of the survey and teachers’ perceptions of their school-level influence, curricular autonomy, and pedagogical autonomy. In addition, the use of SGM measures in teacher evaluation, compensation, or both, statistically significantly negatively predicted both teachers’ pedagogical and curricular autonomy, as well as job satisfaction. These findings are consistent with previous studies that found teachers’ classroom autonomy and job satisfaction to be lessened post-NCLB (Crocco Costigan, 2007; Faulker Cook, 2006; Huss Eastep, 2011).